INTERPOLATING NEURO-FUZZY NETWORK FOR MODELING COLOR RENDERING OF A PRINTING SYSTEM - Bodyansky, E. V.; Kulishova, N. E. (Radio Electronics, Computer Science, Control, 2024)
The architecture and learning algorithm for the neurofuzzy system is proposed. This system is aimed for decision of the interpolation task of two-variable functions, that are known in nodes, which are arbitrary placed on the plane.